6(1 + 3x) = –6x – 18 The answers are No solution X=0 X=-1 X=-3

Question

6(1 + 3x) = –6x – 18
The answers are
No solution
X=0
X=-1
X=-3

in progress 0
Raelynn 1 month 2021-10-18T13:48:13+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-10-18T13:49:15+00:00

    Answer:

    x = -1

    Step by step:

    6(1+3x)=−6x−18

    Step 1: Simplify both sides of the equation.

    6(1+3x)=−6x−18

    (6)(1)+(6)(3x)=−6x+−18(Distribute)

    6+18x=−6x+−18

    18x+6=−6x−18

    Step 2: Add 6x to both sides.

    18x+6+6x=−6x−18+6x

    24x+6=−18

    Step 3: Subtract 6 from both sides.

    24x+6−6=−18−6

    24x=−24

    Step 4: Divide both sides by 24.

    24x

    24

    =

    −24

    24

    x=−1

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )